Validation of molecular markers linked with QTLs for heat and drought stress tolerance in wheat - Singroha, Garima; Mishra, Shefali; Kumar, Satish; Singh, Sanjay Kumar; Singh, Gyanendra; Singh, Gyanendra Pratap; SHARMA, Pradeep (Journal of Cereal Research, 2020)
Global climatic changes affect the production and productivity of wheat around the globe. Increasing heat and drought are the most important abiotic stress factors that hinders productivity. To produce sufficient wheat there is ardent need to develop heat and drought tolerant wheat cultivars; therefore, identification of genetic diversity present among available wheat genotypes using SSRs markers is of prime importance. The allelic variation present among wheat genotypes can be exploited in breeding heat and drought tolerant cultivars. A set of 36 wheat genotypes was evaluated for evaluating genetic diversity for heat and drought tolerance among wheat genotypes using already reported SSR markers. A total of 24 SSR markers were analysed and out of them 19 were found polymorphic. Using SSR markers data cluster analysis was carried out to classify the 34 wheat cultivars for genetic variation in heat tolerance. The dandrogram constructed using SSR markers data assigned the 34 wheat cultivars into three broad clusters. The polymorphic SSRs thus identified could be used to evaluate genetic diversity present among wheat genotypes and the wheat cultivars thus identified genetically diverse could be exploited in wheat breeding programs.